Comparison of debonding resistance and failure type of three orthodontic band cements - Liliana Andrea Piedra-Sarmiento; María Claudia Ariza-Salas; Humberto José Guzmán-Báez; Fernando Zárate-Cadena (Universidad de Antioquia, 2016)
Introduction: the objective of this study was to compare the debonding resistance and failure type observed in three materials used for band cementation by means of the universal testing machine and a stereomicroscope. Methods: 72 third lower molars were collected from patients who needed extractions; metal bands were cemented on them with a pre-soldered tube and internal etching (Bracket USED, OrthoUSA, USA). The samples were randomly sorted out in three groups, forming a control group (zinc phosphate) and two pilot groups (resin-modified glass ionomer and polyacidmodified composite resin). All samples were subjected to a process of 2000 thermal cycles, and later to a debonding resistance test in the universal testing machine (Instron 3367 class 0.5, with 0-30 Kn load cell, USA) at a speed of 2 mm/min. The data were calculated in megapascals, taking into account the surface area of bands (mm2). Finally, to determine failure type, a visual inspection was conducted using a stereomicroscope (Stemi 2000C, Carl Zeiss, Göttingen, Germany AXIOCAM Carl Zeiss Microimaging, Göttingen, Germany). Results: no statistically significant differences were found among the three study groups in terms of debonding resistance (p value = 0.119). The most predominant failure type in the three cements occurred at the cemento-enamel interphase, with 61.1%, showing a statistically significant difference. Conclusion: zinc phosphate, resin-modified glass ionomer and polyacid-modified composite resin showed similar debonding resistance values and the most predominant failure type in the three band cementing materials occurred at the cemento-enamel interface; however, the resin-modified glass ionomer showed a lower percentage.